2006
DOI: 10.1897/2512039.1
|View full text |Cite
|
Sign up to set email alerts
|

Selenite transport and its inhibition in the unicellular green alga Chlamydomonas reinhardtii

Abstract: The influence of time, ambient concentration, and medium composition on selenite (Se(IV)) uptake by the unicellular green alga Chlamydomonas reinhardtii has been investigated. The aims of the performed experiments were to describe the kinetics of accumulation, to characterize transport capacities, to identify key nutrients influencing absorption, and to establish links between speciation and bioavailability. Our results suggested that the adsorbed fraction was negligible compared to the absorbed one. Over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 38 publications
(70 reference statements)
1
42
0
Order By: Relevance
“…We measured a significant ( p < 0.05) pH effect on Se accumulation by C. reinhardtii (Figure B) following 12 h of exposure to 63 nM Se(IV). In contrast, 2 other studies on this algal species reported no clear influence of pH on Se(IV) accumulation (Morlon et al [pH 5–8]; Riedel and Sanders [pH 5–9]). The pH effect that we measured can be explained by the fact that Se(IV) speciation changes markedly as pH increases from 7 to 9 because the protonated form (HSeO 3 – ) is progressively replaced by the deprotonated form (SeO 3 2– ) up to pH 8.4 (p K a ), at which point approximately 50% of each Se(IV) species is present (thermodynamic calculation using MINEQL+; Schecher and McAvoy ).…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…We measured a significant ( p < 0.05) pH effect on Se accumulation by C. reinhardtii (Figure B) following 12 h of exposure to 63 nM Se(IV). In contrast, 2 other studies on this algal species reported no clear influence of pH on Se(IV) accumulation (Morlon et al [pH 5–8]; Riedel and Sanders [pH 5–9]). The pH effect that we measured can be explained by the fact that Se(IV) speciation changes markedly as pH increases from 7 to 9 because the protonated form (HSeO 3 – ) is progressively replaced by the deprotonated form (SeO 3 2– ) up to pH 8.4 (p K a ), at which point approximately 50% of each Se(IV) species is present (thermodynamic calculation using MINEQL+; Schecher and McAvoy ).…”
Section: Resultsmentioning
confidence: 63%
“…Kelly Lake (Figure ) differed somewhat from the other lakes in that adding Se(VI) concentrations (solid triangles in Figure ) to Org‐Se concentrations (solid squares in Figure ) overpredicted [Se] in organisms from this lake. The high SO 4 concentrations in this lake (4 mM) likely competed with those of inorganic Se, thereby reducing the accumulation of inorganic Se species at the base of the food chain (Figure C; Morlon et al ; Fournier et al ; Ponton and Hare ). To explain these trends seen in nature, we explored the influence of Se speciation, SO 4 , and H + on [Se] in the green alga C reinhardtii .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Others have identified that Se concentration of rice roots had a close negative correlation to nitrate concentration (R 2 =0.7252), due to anion-anion interactions (Xu et al 2010). Similarly, nitrate was also found to inhibit selenite uptake in the unicellular green alga Chlamydomonas reinhardtii (Morlon et al 2006).…”
Section: Discussionmentioning
confidence: 93%